Bioimpedance spectroscopy: A technique to monitor interventions for swelling in minor burns - Kenworthy, P.; Grisbrook, Tiffany; Phillips, M.; Gittings, P.; Wood, F.; Gibson, W.; Edgar, D. (Pergamon Press, 2017)
The control of edema in burn injured patients is a priority as it can impede the wound healing process. Bioimpedance spectroscopy (BIS) has been identified as a method of swelling assessment that has merit after burns. The aim of this study was to examine the reliability and validity of BIS in the measurement of localised burn wound edema across (1) different dressing conditions (no dressing, non silver and silver dressings) and (2) three electrode positions. BIS resistance (R) was hypothesised to be inversely proportional to fluid (edema) volume. BIS was collected in triplicate for all conditions of interest. BIS repeated measures demonstrated excellent concordance for all BIS resistance variables (R0, Ri, Rinf) (intraclass correlation coefficient = 0.999–1.00, 95% confidence intervals 0.999–1.00) without a systematic difference. Multilevel mixed effects linear regression analysis examined the effect of electrode position and dressing condition on BIS resistance variables. R0, Ri and Rinf significantly increased with decreasing localised limb segment volume (p ≤ 0.01). Resistance was significantly (1) reduced when a silver dressing was in situ (p < 0.01) and (2) increased when a non-silver dressing was insitu (p < 0.01). There was a significant interaction between each dressing condition and localised limb segment volume (p < 0.01). An algorithm was developed to adjust resistance values when a silver dressing is in use. BIS may be used clinically to monitor localised changes in burn wound edema.